Experimental study on smoke control using wide shafts in a natural ventilated tunnel. Issue 195 (December 2019) - He, Kun; Cheng, Xudong; Zhang, Shaogang; Yao, Yongzheng; Peng, Min; Yang, Hui; Cong, Wei; Shi, Zhicheng; Chen, Zhengquan
Abstract: Natural ventilation using vertical shafts shows a growing popularity in urban tunnel and metro tunnel due to less energy cost and no need for maintenance. In order to study its reliability, a number of tests were conducted to investigate the characteristics of the smoke inside the tunnel and complete smoke exhaustion under natural ventilation using a wide vertical shaft in metro tunnel fires. The results indicated the smoke temperature behind the wide shaft would decrease with increasing the shaft height, accompanied by thinner smoke layer thickness. Besides, there exists a critical vertical shaft height existed allowing a complete smoke exhaustion. When the shaft height exceeded the critical vertical shaft height, a safe evacuation environment behind the shaft could be guaranteed. A theoretical model of calculating the critical condition for exhausting total fire smoke was established based on the experimental results. It should be noted that this model does not consider the inclination of the tunnel, vehicle movement and extreme meteorological effects on the portals. And the equivalent HRRs are 1.75–6.98 MW in a full-scale tunnel. The results of this paper can provide guide for the ventilation design of metro tunnel in the future. Highlights: The thermal properties under natural ventilation using a wide shaft was addressed. There exists a critical vertical shaft height allowing complete smoke exhaustion. The critical vertical shaft height is independent from the fire size. A model was developed to predict the complete smoke exhaustion.